2019
DOI: 10.1007/s11904-019-00436-7
|View full text |Cite
|
Sign up to set email alerts
|

Medications for Treatment of Opioid Use Disorder among Persons Living with HIV

Abstract: Purpose of Review Recent HIVoutbreaks have occurred as a result of the current US opioid epidemic. Providing medications for opioid use disorder (MOUD) with methadone, buprenorphine, and extended-release naltrexone is essential to achieving optimal HIV treatment outcomes including viral suppression and retention in treatment. This review describes the pharmacology of MOUD with specific attention to interactions with antiretroviral therapy, and to the effect of MOUD on HIV treatment outcomes. Recent Findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 51 publications
1
31
0
Order By: Relevance
“…147 However, multiple studies have found that treatment with methadone or buprenorphine is associated with improved HIV treatment outcomes and decreased all cause mortality. [148][149][150] A systematic review and meta-analysis of 32 studies found that treatment with methadone or buprenorphine enhanced patient recruitment on to antiretroviral therapy (hazard ratio 1.69, 1.32 to 2.15), adherence to antiretroviral therapy (odds ratio 2.14, 1.41 to 3.26), and HIV viral suppression (odds ratio 1.45, 1.21 to 1.73). 150 Chronic HCV infection is common among people with OUD, especially those with a history of injecting drug use.…”
Section: Special Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…147 However, multiple studies have found that treatment with methadone or buprenorphine is associated with improved HIV treatment outcomes and decreased all cause mortality. [148][149][150] A systematic review and meta-analysis of 32 studies found that treatment with methadone or buprenorphine enhanced patient recruitment on to antiretroviral therapy (hazard ratio 1.69, 1.32 to 2.15), adherence to antiretroviral therapy (odds ratio 2.14, 1.41 to 3.26), and HIV viral suppression (odds ratio 1.45, 1.21 to 1.73). 150 Chronic HCV infection is common among people with OUD, especially those with a history of injecting drug use.…”
Section: Special Populationsmentioning
confidence: 99%
“…Moreover, people with SUD have been found to have decreased rates of appropriate CD4 cell monitoring (80.0% v 70.9%; P=0.001), appropriate pneumocystis pneumonia prophylaxis (95.0% v 90.1%; P=0.016), HIV viral suppression (51.9% v 41.4%; P<0.001), and vaccinations (pneumococcal conjugate vaccine 23 vaccination rates 89.3% v 84.6%; P<0.001) 147. However, multiple studies have found that treatment with methadone or buprenorphine is associated with improved HIV treatment outcomes and decreased all cause mortality 148149150. A systematic review and meta-analysis of 32 studies found that treatment with methadone or buprenorphine enhanced patient recruitment on to antiretroviral therapy (hazard ratio 1.69, 1.32 to 2.15), adherence to antiretroviral therapy (odds ratio 2.14, 1.41 to 3.26), and HIV viral suppression (odds ratio 1.45, 1.21 to 1.73) 150…”
Section: Treatmentmentioning
confidence: 99%
“…There is a consensus that opioid substitution therapies; namely, buprenorphine and methadone, are associated with reductions in overdose and serious opioid-related acute care use compared with other treatments including among PLWH [ 80 , 81 ]. Moreover, both buprenorphine and methadone improve HIV viral suppression, adherence to antiretroviral therapy, and overall mortality for PLWH with opioid use disorder, along with improved stability and quality of life, reductions in opioid use and relapse, and reductions in the transmission of HIV infections to others [ 82 – 86 ]. Further, extended-release naltrexone has been studied in PLWH leaving incarcerated settings and improves HIV viral suppression in that context [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, both buprenorphine and methadone improve HIV viral suppression, adherence to antiretroviral therapy, and overall mortality for PLWH with opioid use disorder, along with improved stability and quality of life, reductions in opioid use and relapse, and reductions in the transmission of HIV infections to others [ 82 – 86 ]. Further, extended-release naltrexone has been studied in PLWH leaving incarcerated settings and improves HIV viral suppression in that context [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…In neglecting the general population for prevention messaging in favour of key populations, we exclude both those who are not easily reached by more targeted communication strategies and those who can help catalyze and sustain a supportive and enabling environment. This applies as much to biomedical prevention interventions [28] as to condom promotion.…”
Section: Plos Onementioning
confidence: 99%